Implementation of Directive Functions in Children's Literature Written by Authors of Children Aged 7-12 Years - Cholis Mawanti; Nensy Megawati Simanjuntak; Suyatno; Darni (PT FORMOSA CENDEKIA GLOBAL, 2023)
A work of fiction made by a child is an extraordinary gift. The child's ability to imagine and put that imagination into a series of stories is an invaluable value of the archipelago's wealth. A work made by children aged 6-12 years became one of the riches of Indonesian literature which eventually developed and was called children's literature. Children's literature is rich in values and messages. Children's literature is also rich in directive functions. This study found that in children's literature there are many directive functions conveyed by the author through his work. The various directive functions contained in children's fiction are representations of real life experienced by characters or writers in their daily routines. The richer the directive function in children's fiction, the richer the message conveyed by the author, implicitly or explicitly